Cloning of genes encoding a 15,000-dalton peptidoglycan-associated outer membrane lipoprotein and an antigenically related 15,000-dalton protein from Haemophilus influenzae. - Deich, R A (1988)
We have cloned and expressed in Escherichia coli a gene encoding a 15,000-apparent-molecular-weight peptidoglycan-associated outer membrane lipoprotein (PAL) of Haemophilus influenzae. The nucleotide sequence of this gene encodes an open reading frame of 153 codons with a predicted mature protein of 134 amino acids. The amino acid composition and sequence of the predicted mature protein agree with the chemically determined composition and partial amino acid sequence of PAL purified from H. influenzae outer membranes. We have also identified a second gene from H. influenzae that encodes a second 15,000-apparent-molecular-weight protein which is recognized by antiserum against PAL. This protein has been shown to be a lipoprotein. The nucleotide sequence of this gene encodes an open reading frame of 154 codons with a predicted mature protein of 136 amino acids and has limited sequence homology with that of the gene encoding PAL. Southern hybridization analysis indicates that both genes exist as single copies in H. influenzae chromosomal DNA. Both genes encode polypeptides which have amino-terminal sequences similar to those of reported membrane signal peptides and are associated primarily with the outer membrane when expressed in E. coli.